A Simultaneous Dispersive Liquid-Liquid Microextraction-complexation Method to Determine Trace Cobalt in Chamomile Tea Extract Prior to Slotted Quartz Tube Flame Atomic Absorption Spectrometry - Bakirdere, Emine Gulhan; Akarcay, Nur Azize; Zaman, Buse Tugba; Bakirdere, Sezgin (OXFORD UNIV PRESS, 2020)
A novel and effective analytical method was developed for the determination of trace cobalt by slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS) after simultaneous dispersive liquid-liquid microextraction (S-DLLME) based on contemporaneous complexation and extraction. Approximately 48 times enhancement in detection power was recorded based on the comparison of detection limits of the developed system (4.7 ng/mL) with the detection power of the conventional FAAS. Percent relative standard deviation for the lowest concentration was calculated as 3.8%. Spiked recovery experiments on chamomile tea extract samples were carried out to determine applicability of the developed method to real sample matrix. Percent recovery results for two different concentrations were approximately 100%, with standard deviation values below 10%.
Keywords: Cobalt; Flame atomic absorption spectrometry; Slotted quartz tube; PHASE MICROEXTRACTION; SAMPLES; PRECONCENTRATION; ELEMENTS; NICKEL; COPPER; IONS; Chemistry